Genome Sequencing of Hericium coralloides by a Combination of PacBio RS II and Next-Generation Sequencing Platforms - Caixia Zhang; Lijun Xu; Jian Li; Jiansong Chen; Manjun Yang (International Journal of Genomics)
The fruiting bodies or mycelia of Hericium coralloides (H. coralloides) contain many physiologically active compounds that are used to treat various diseases, including cardiovascular disorders and cancers. However, the genome of H. coralloides has not been sequenced, which hinders further investigations into aspects, such as bioactivity or evolutionary events. The present study is aimed at (i) performing de novo sequencing of the assembled genome; (ii) mapping the reads from PE400 DNA into the assembled genome; (iii) identifying the full length of all the repeated sequences; and (iv) annotating protein-coding genes using GO, eggNOG, and KEGG databases. The assembled genome comprised 5,59,05,675 bp, including 307 contigs. The mapping rate of reads obtained from PE400 DNA in the assembled genome was 92.46%. We identified 2,525 repeated sequences of 14,23,274 bp length. We predicted ncRNAs of 48,895 bp and 11,736 genes encoding proteins that were annotated in the GO, eggNOG, and KEGG databases. We are the first to sequence the entire H. coralloides genome (NCBI; Assembly: ASM367540v1), which will serve as a reference for studying the evolutionary diversification of edible and medicinal mushrooms and facilitate the application of bioactivity in H. coralloides.